Herramientas Biotecnológicas para realizar el mejoramiento genético vegetal (2021)
Infografía también disponible en: https://view.genially.com/5f0bca7c63b7ef0dac72f535/interactive-image-cartelera-autocuidado-y-profesionales-de-la-salud?fbclid=IwAR0O92bFtMmWQtAR1Q8I0bLaUYsnoYFcm0izrLMBo4cVcJd8nHN9-uDjisM